2018
DOI: 10.1038/s41598-018-35825-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the neuroprotective effect of AAV-mediated β-synuclein overexpression in a transgenic model of synucleinopathy

Abstract: Parkinson’s disease (PD) and multiple system atrophy (MSA) are neurodegenerative diseases characterized by inclusions mainly composed of α-synuclein (α-syn) aggregates. The objective of this study was to investigate if β-synuclein (β-syn) overexpression could have beneficial effects by inhibiting the aggregation of α-syn. The M83 transgenic mouse is a model of synucleinopathy, which develops severe motor symptoms associated with aggregation of α-syn. M83 neonate or adult mice were injected with adeno-associate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…We found that intracerebral inoculations of brain extracts from old and sick M83 mice drastically accelerated the onset of paralysis that typically develops during the ageing of these mice [7]. These observations were then confirmed in a number of other studies, either after intracerebral inoculations of fibrillar recombinant aS [8][9][10] or of brain extracts from human patients, notably with MSA [11][12][13]. Other studies used different peripheral inoculation routes [14][15][16][17] with similar findings.…”
Section: Introductionsupporting
confidence: 80%
“…We found that intracerebral inoculations of brain extracts from old and sick M83 mice drastically accelerated the onset of paralysis that typically develops during the ageing of these mice [7]. These observations were then confirmed in a number of other studies, either after intracerebral inoculations of fibrillar recombinant aS [8][9][10] or of brain extracts from human patients, notably with MSA [11][12][13]. Other studies used different peripheral inoculation routes [14][15][16][17] with similar findings.…”
Section: Introductionsupporting
confidence: 80%
“… 27 They also include beta‐synuclein, which plays a detrimental role in Alzheimer's disease and Parkinson's disease. 28 Nevertheless, agents that have the potential to reduce excitotoxicity are currently under investigation as promising HIE therapies. 29 …”
Section: Discussionmentioning
confidence: 99%
“…For patients with lifelong genetic disorders, such a decrease could reduce the concentration of gene products outside the therapeutic window. On the other hand, simply increasing the dose of AAV at the first administration may lead to vector toxicity 26 , an immune response against both vector 27 and transgene 28 , and potentially the side effects from overexpression of the transgene 29 .…”
Section: Introductionmentioning
confidence: 99%